Pemanfaatan gamifikasi dalam pendidikan anti korupsi: Upaya membangun kesadaran generasi z di era digital - Faizy, Azmi (Maliki Interdisciplinary Journal, 2026)
Corruption remains a major challenge hindering Indonesia’s national progress. Combating corruption cannot rely solely on legal enforcement; it must also encompass education from an early age, particularly targeting Generation Z as the nation’s future. Unfortunately, conventional approaches to anti-corruption education have proven insufficient in engaging a generation raised in the midst of rapid digitalization. This article examines the potential of gamification as an innovative approach in anti-corruption education to foster awareness among Generation Z in the digital era. The study employs a literature review methodology, drawing on various relevant academic journals and books. Findings indicate that the application of gamification elements such as points, levels, and challenges successfully enhances motivation, active participation, and learners’ understanding of integrity and anti-corruption values. Gamification in the context of anti-corruption education proves relevant and well-targeted for Generation Z. Therefore, this approach deserves consideration as a creative and innovative alternative in strengthening anti-corruption education in the digital era.